Genetic variants of vitamin-D receptor genome and teeth caries susceptibility in Iraqi children - Al-Hadithi, Haraa Khairi; Abdul-Wahab, Ghasaq Asim; Abbas, Maha Jamal; Al Nuaimy, Zaineb Amjed (Brazilian Dental Science, 2024)
Objective: To find out if there is a link between the TaqI, ApaI, BsmI, and FokI polymorphisms of the vitamin D receptor (VDR) and dental caries risk in Iraqi children. Material and Methods: The study had a sample of one hundred children, consisting of fifty males and fifty females, their mean age of 10.2 ± 1.21 years old. The study volunteers were categorized into two groups: a moderate caries risk group (DMFT, 1-4) consisting of 50 individuals, and a caries-free group including 50 individuals. Salivary samples were obtained from each participant, and subsequent DNA extraction was performed. The VDR gene was geno-typed using the polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) techniques. All data were subjected to statistical analysis using the chi square test, Fisher’s exact test, and Odds ratios; results considered significant when (P